Sustainable Tourism Villages in the Perspective of Social Construction Empowerment Based on Tourism Awareness Groups in Gowa Regency - Nur Riswandy Marsuki, Darman Manda, Najamuddin, Syamsu. A. Kamaruddin (South Eastern European Journal of Public Health, 2025)
This study provides an overview of the social construction of community-based empowerment in tourist villages in Gowa Regency. This community empowerment needs to be intervened through an integrative and sustainable approach by demanding integration in the aspects of Education, social, culture/history, economy, and environment and involving collaboration between government, community, universities, media and the private sector so as to encourage the acceleration of sustainable tourism village development. The purpose of this study was to analyze community involvement patterns, explore community empowerment practices and formulate social construction designs in the development of sustainable tourism villages based on integrative community empowerment in Gowa Regency. This study used qualitative methods, researchers as key instruments, determination of informants using purposive sampling techniques, data collection through observation, documentation studies, in-depth interviews and focus group discussions (FGD), data analysis using interactive models including data reduction, data presentation, verification and drawing conclusions. The results of the study found that: 1. Community participation patterns consist of 3 forms, namely a. Pseudo/passive participation where the community only fulfills the formalities of administrative needs, b. Technical participation that there has been community involvement but the final decision remains with the village government or the private sector and c. Active participation where full control and access to decisions in tourism development lies with the community. 2. Community empowerment practices through; a. Increasing community capacity through education and training, b. Reactivation of discussion forums through tourism awareness groups (Pokdarwis) related to tourism development in the village, c. Preservation of culture, environment and strengthening the identity of tourism villages through organizing music, culture and sports events/festivals. 3. Design of social construction based on integrative community empowerment through the stages; a. Externalization by identifying and mapping village potential, b. Objectivation of efforts to strengthen the social and institutional structure of tourism awareness groups (Pokdarwis), c. Internalization through community involvement, capacity building and building external networks, d. Activation/implementation of empowerment programs that have been mutually agreed upon and e. Evaluation by measuring periodically and taking good practices as learning. This social construction will have implications for the development of sustainable tourism villages towards empowered and independent villages.